Scarcity, conflict and environmental crime - Uhm, Daan P. van (Criminological connections, directions, horizons, 2025)
The chapter is dedicated to the important work of Nigel South on green criminology and responds to the call for empirical research into the relationship between scarcity, conflict, and environmental crime (South 2014; Beirne & South 2007; Brisman & South, 2013). Based on empirical research in three violent landscapes around the world - the Darién Gap, the Golden Triangle, and the eastern edge of the Congo Basin - it provides new insights into the link between humans and environmental degradation associated with conflicts over natural resources. The empirical findings will be analysed by a four-pronged typology of conflict-environment relationships, introduced by Nigel South - together with Avi Brisman and Rob White (2016) - which is important to untangle the conflicts. The results will shed light on the colonial, geopolitical and socioeconomic contexts in these biodiverse areas to understand the conflicts over natural resources from a green criminological perspective.